Upward dead-end filtration of solid/liquid mixture containing fine-bubbles - Tanaka, Takanori; Ubukata, Hikaru; Yoshimoto , Akihiko; Jami, Mohammed Saedi; Iwata, Masashi (2016)
Microscopic bubbles with diameter <50 μm are generally called fine-bubbles and have different behaviors from ordinary bubbles. For example, very long stagnation time and having pressurized interior gas due to surface tension are characteristics of fine-bubbles. In this study, to evaluate the effects of fine-bubble-bodyfeeding on filtration properties, upward dead-end filtration test (where filtration and sedimentation take place in opposite directions) of clay suspension containing fine-bubble was conducted. Fine-bubbles were generated by the high speed shearing method. The mixture of kaolin clay suspension and fine-bubbles dispersed in water was filtered under constant-pressure conditions. During the upward dead-end filtration, part of the filter cake was detached from the surface of the filter cake because of gravity. Based on the difference between the modified Ruth plots of upward and downward filtration, the detached cake mass from the surface of the filter cake during the upward filtration was evaluated. Fine-bubble-bodyfeeding enhanced the kaolin cake detachability from the surface of the filter cake over the filtration time.